COBLL1, LPL and ZAP70 expression defines prognostic subgroups of chronic lymphocytic leukemia patients with high accuracy and correlates with IGHV mutational status. Issue 1 (2nd January 2017) - Plesingerova, Hana; Librova, Zuzana; Plevova, Karla; Libra, Antonin; Tichy, Boris; Skuhrova Francova, Hana; Vrbacky, Filip; Smolej, Lukas; Mayer, Jiri; Bryja, Vitezslav; Doubek, Michael; Pospisilova, Sarka
Abstract: The clinical course of chronic lymphocytic leukemia (CLL) is highly variable. Patients with unmutated IGHV (U-CLL) usually progress rapidly, whereas patients with mutated IGHV (M-CLL) have a more indolent disease. The expression of several genes correlates closely with the IGHV mutational status and could be used to assess prognosis in CLL. We analyzed the prognostic relevance of COBLL1, LPL, and ZAP70 gene expression, which correlated with IGHV mutational status ( p < 0.0001), in 117 CLL patients and established a prognostic parameter dividing the tested cohort according to the disease aggressiveness. Our prognostic parameter was validated on an independent cohort of 161 CLL patients and achieved a high accuracy (94%). Patients divided according to the prognostic parameter differ in overall survival and time to first treatment ( p < 0.0001, HR = 2.300/5.970, 95% CI: 1.587–3.450/4.621–15.86). Our approach provides a reliable alternative method to prognosis assessment via IGHV mutational status analysis.